Strategi Mempertahankan Loyalitas Pelanggan Usaha Rara Laundry - Rahmadani, Inna Ludvia; Ningrum, Nurita Kustiari (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
Loyalty is a customer's commitment to a product or service as measured by repurchasing. Customer loyalty has an important role in a company. Maintaining them means improving financial performance and maintaining the viability of a company. This is the main reason for a company, to attract and retain customers. This study uses a qualitative descriptive approach aimed at describing and drawing the phenomena that exist in the field regarding strategies to maintain customer loyalty. With data collection techniques through interviews, observation and documentation. Based on the results of the research, it shows that the strategy to maintain customer loyalty in the Rara Laundry business is said to be good, because it is in accordance with the theory of strategy to build customer loyalty. However, in reality, a good strategy has not been able to maintain customer loyalty. It is concluded that the supporting factors have not fully maintained customer loyalty. While the inhibiting factors from external parties dominate the level of customer loyalty. Keywords: Strategy, loyalty